The Power of Civilization: The Role of Civilized Cities in Corporate ESG Performance - Qi, Zhenyu; Zhang, Enqi; Wang, Chuncao; Liu, Wei (Frontiers in Environmental Science, 2022)
Civilization usually has a societal impact that is created by well-integrated members of society. The present study argues that government-led construction of a national civilized city encourages enterprises to assume more ESG investments, including social and environmental practices. Based on panel data of Chinese listed firms, we found that if the firm’s residence is rated as a national civilized city, the corporate ESG performance improves. This effect is only significant for environmental practices, which are easily quantified and of high concern for the government. In addition, this positive effect is only significant in state-owned firms with a close relationship with the government. We also found that the spotlight effect of the media is an essential guarantee for civilized city policies to improve corporate ESG performance. This study confirms the role of government-led civilized city construction as a soft restraint mechanism in enhancing corporate environmental practices, but also found that there is insufficient motivation for other social responsibilities. These findings expand research on the influencing factors of corporate ESG performance.